About regularities of technological parameters influence on accident–free mining of flat coal seams by plow systems - Demydov, M.S.; Shapovalov, Ya.A.; Astafiev, D.O.; Demchenko, Yu.I. (Розробка родовищ, 2014)
Analysis of research and publication on concerned topic is given. Analysis of stratigraphic columns of investigated seam is executed. Distance influence from wall face on loading character of mechanized support sections is determined. Regularities of loading changing on support sections at different advance rate of stoping face are substantiated.